Release of Soluble Interleukin-7 α Receptor (CD127) from CD8+ T-Cells and Human Thymocytes - Sanchez Vidales, Maria Del Mar (Université d'Ottawa / University of Ottawa, 2016)
ABSTRACT Background Interleukin-7 (IL-7) is a cytokine crucial for T-cell development and homeostasis. IL-7 is thought to be a limited resource, and its interaction with the IL-7 receptor (IL-7R) has effects on increasing cell survival, proliferation and cytolytic function. Considering the roles of IL-7, it is no surprise that the expression of the IL-7 receptor alpha chain (CD127) is tightly regulated. Despite increased levels of soluble CD127 (sCD127) being detected in a number of disease states and being associated with disease activity, the biological function of sCD127 and its clinical relevance remains to be established. In this study, I explore the post-translational mechanisms leading to the release of the soluble form of CD127 receptor through IL-7 and αCD3/αCD28 stimulation. Here I specifically established two different mechanisms by which CD127 is processed; shedding of the receptor ectodomain and clipping. Results In CD8+ T-cells, IL-7 plus TcR stimulation resulted in an increased release of sCD127. Here I found that matrix metalloproteases (MMPs), in particular MMP-9, have a role in the proteolytic clipping of CD127 resulting in the release of sCD127. In addition, I found that IL-7 plus TcR stimulation resulted in an increase in MMP activity and this activity was particularly dampened when MMP-2 and -9 inhibitors were used. I also found that neither MMP-3 nor cysteine and serine proteases seem to be directly involved in the generation of sCD127. Using a biotinylation assay I found that CD127 is being shed from the surface of CD8+ T-cells as well as thymocytes through a MMP-independent mechanism. Conclusion These results demonstrate that MMPs (in particular MMP-9) have a role in the generation of sCD127. Further studies are required to determine the specific sheddase responsible for the ectodomain shedding of CD127, as well as the details behind the regulation of MMP-9 activity both in CD8+ T-cells and thymocytes. A thorough understanding of these mechanisms will aid in the development of alternative and more specific strategies to control IL-7 mediated processes in both normal and disease states.
Keywords: IL-7; MMPs; CD8+ T cells; Thymocytes; CD127